Permanent ferroelectric retention of BiFeO3 mesocrystal - Ying-Hui Hsieh (Nature Portfolio, 2016)
Ferroelectric reliability must be solved prior to practical non-volatile electronic devices based on magnetoelectric multiferroics. Here, Hsiehet al. report a long lasting ferroelectric retention in the heteroepitaxially constrained multiferroic mesocrystal.